The level of motor fitness and skills among future early-education teachers - Podstawski, Robert; Górnik, Katarzyna; Romańczuk, Agnieszka (Polish Journal of Public Health, 2013)
Introduction. The Polish law is giving the entitlement for conducting the physical education classes to both graduates of physical education, as well as the teachers of early education. The duty of teachers working with children is to provide knowledge, developing the skills and attitudes related to strengthening health of students. Physical education teacher by acting on the personality and the body of his pupils should also be a personality model for them. The teacher should have an appropriate level of the motor skills enabling to show the technique of performing the exercise.Aim. The aim of this study was to examine the level of motor fitness and skills of teachers studying at postgraduate level in the field of integrated early education.Material and methods. The study was performed in a group of 82 active teachers who instructed execution of 8 tests of motor skills and 12 exercises used in teaching kindergarten children and early education classes.Results. The study showed the presence of the average and low-level motor skills in women. In 67% of the studied cases, women could not demonstrate basic motor skills to the children being taught by them.Conclusions. Physical education classes for preschoolers and 1st-3rd graders should be conducted by experts in the field. Very low level of motor fitness and skills determined by the present study, it can be concluded that future early-education teachers are ill-prepared for carrying out such a responsible role